Implementasi Sistem Informasi Manajemen Berbasis Teknologi Cloud untuk Peningkatan Produktivitas dan Efisiensi Bisnis - Geubrina Raseuki; Muhammad Irwan Padli Nasution (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
The aim of this research is to determine the implementation of an information technology-based management system at North Sumatra State University, seen from the aspects of communication, resources and attitudes of implementers. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation and documentation studies. The research results show that the implementation of an information technology-based management information system at UINSU from the communication aspect has not been effective. This can be seen from the low level of understanding from top management to implementers regarding clarity of content, objectives, direction, target groups, and specific division of information tasks regarding the implementation of an information technology-based management information system. Judging from the aspect of resources (human and financial), it is less effective. This can be seen from the quantity of professional management human resources which is still lacking, the quality of management human resources is less innovative and creative in developing application systems, and the existing financial support is limited to minimum service standards. Judging from the aspect of the implementer's attitude, it shows resistance in terms of less than optimal service and network performance as a result of inaccessibility to all units within the UINSU environment.